2002
DOI: 10.1023/a:1020660124582
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Automatic samplers are a common method of data collection for numerous monitoring projects in the South Florida region and elsewhere. Although total phosphorus (TP) is the primary parameter of interest within this region, nitrogen species such as ammonia nitrogen (NH4-N), nitrate+nitrite nitrogen (NOx-N), and total kjeldahl nitrogen (TKN) are also collected and analyzed. Federal and state quality assurance guidelines require nutrient samples to be preserved by acidification with H2SO4 to a pH < 2 and stored im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The concentrations for both pond and stream water were variable, increasing by as much as 9.92% on Day 1 for stream water and decreasing by as much as 6.25% on Day 7 for stream water. Overall, the findings in this study are in agreement with other studies that found sulfuric acid to be a sufficient preservative for nitrate-N for up to seven days [10]. However, this study indicates suitability of sulfuric acid to preserve samples for up to 14 days.…”
Section: Nutrient Concentrations From Preserved Samplessupporting
confidence: 92%
See 2 more Smart Citations
“…The concentrations for both pond and stream water were variable, increasing by as much as 9.92% on Day 1 for stream water and decreasing by as much as 6.25% on Day 7 for stream water. Overall, the findings in this study are in agreement with other studies that found sulfuric acid to be a sufficient preservative for nitrate-N for up to seven days [10]. However, this study indicates suitability of sulfuric acid to preserve samples for up to 14 days.…”
Section: Nutrient Concentrations From Preserved Samplessupporting
confidence: 92%
“…In contrast, a study found that while refrigeration and filtration were necessary, acidification was the most effective preservation method for nitrate-N [9]. Sulfuric acid can serve as a sufficient preservative for maintaining nitrate-N and total N concentrations for up to seven days [10], but may be unsuitable for samples containing high concentrations of nitrite because sulfuric acid can cause the chemical conversion to nitrate [11]. Furthermore, a study in California, USA, found that long-term freezing can serve as a viable method, as it did not have a significant effect on concentration [12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reduced N excretion in pig slurry is closely associated with decrease in the odour emission from pig facilities [ 39 ]. Total Kjeldahl nitrogen (TKN) is the sum of organic nitrogen, ammonia (NH3), ammonium (NH4) and therefore to calculate total nitrogen, concentration of nitrate-N and nitrite-N needs to be determined and added to TKN [ 40 ]. Total N and TKN levels, interestingly, tended to be lower but ammonium nitrogen (NH 4 -N) was higher in 2012 group than in 2007 group in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, automatic water samplers can be used for time series acquisition (e.g. hourly or daily) (Burke et al 2002). This approach has provided insights into temporal nutrient dynamics on the time-scales of hydrological responses in agriculturally dominated catchments (Bieroza et al 2014;Bieroza and Heathwaite 2015).…”
Section: Introductionmentioning
confidence: 99%